Emission color-tunable oxazol(in)yl-substituted excited-state intramolecular proton transfer (ESIPT)-based luminophores. Issue 98 (24th November 2020) - Göbel, Dominik; Rusch, Pascal; Duvinage, Daniel; Bigall, Nadja C.; Nachtsheim, Boris J.
Abstract : Oxazolinyl- and arylchalcogenazolyl-substituted hydroxyfluorenes exhibiting excited-state intramolecular proton transfer (ESIPT) are described as potent and highly modular luminophores. Abstract : Oxazolinyl- and arylchalcogenazolyl-substituted hydroxyfluorenes exhibiting excited-state intramolecular proton transfer (ESIPT) are described as potent and highly modular luminophores. Emission color tuning was achieved by varying the π-expansion and the insertion of different chalcogen atoms.